RANCANG BANGUN APLIKASI AGROBISNIS MARKETPLACE BERBASIS LOKAL “AGRITION” AGRICULTURE SOLUTION - Ade Hendini; Yuza Fahrul Mujtahid (Jurnal Informatika Kaputama (JIK), 2020)
Food needs are very important, but how about if there is a food is difficult to find in the local market. Problems arise because of difficulties in finding stalls or other markets that have food or agricultural products to be sought. By looking back at the development of various types of marketplaces in this era, it would be very helpful to create a locally-based marketplace, which only displays food products in the surrounding area, so that it can provide opportunities for local farmers to market their products. "AGRITION" WEB-BASED AGRICULTURE SOLUTION is a web application in the form of a marketplace that is designed to facilitate consumers in finding products or locations of food or farm stalls in Pontianak according to the needs of Sellers and Buyers. By using the PHP programming language and MySQL database. The researcher designed the design using ERD (Entity Relationship Diagram) and LRS (Logical Record Structure) along with components such as entities, attributes and their relationships.